International Peacebuilding and Local Resistance - Mac Ginty, Roger. author. aut Link
XI, 240 p.
Keywords: Using the case studies of Afghanistan, Iraq, Bosnia, Lebanon and Northern Ireland this book dissects internationally-supported peace interventions. Looking at issues of security, statebuilding, civil society and economic and constitutional reform, it proposes using the concept of hybridity to understand the dynamics of societies in transition.